Effects of forest management on epiphytic lichen diversity in Mediterranean forests - Aragón, Gregorio; Martinez, I.; Izquierdo, P.; Belinchon, R.; Escudero, A. (APPLIED VEGETATION SCIENCE, 2010)
Question What are the responses of epiphytic lichens to the intensity of management along a large environmental gradient in Mediterranean Quercus forests? Location Central Spain. Methods This study was carried out on 4590 trees located in 306 forest stands dominated by Quercus faginea or Quercus ilex ssp. ballota. The effect of forest management and other predictor variables on several species diversity indicators were studied. Variables modelled were total species richness, cyanolichen richness and community composition. A large number of predictor variables were included: forest fragmentation (patch size, stand variability), climate and topographic (altitude, slope, sun radiation, annual rainfall and mean annual temperature) and intensity of management. General linear models and constrained ordination techniques were used to model community traits and species composition, respectively. Results Total richness and especially cyanolichens richness were significantly and negatively affected by the intensity of management. Lichen composition was influenced by management intensity, climatic and topographic variables and stand variability. Conclusions In Mediterranean forests, human activities related to forestry, agricultural and livestock use cause impoverishment of lichen communities, including the local disappearance of the most demanding species. The conservation of unmanaged forests with a dense canopy is crucial for lichen diversity.
The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL PUBLISHING, INC
Keywords: Community traits; Cyanolichens; Drivers of composition; fragmentation; land use; oak forests; Spain; Variation partitioning

Fragmentation, habitat composition and the dispersal/predation balance in interactions between the Mediterranean myrtle and avian frugivores - González-Varo, Juan P. (Ecography, 2010)
Human-induced fragmentation and disturbance of natural habitats can shift abundance and composition of frugivore assemblages, which may alter patterns of frugivory and seed dispersal. However, despite their relevance to the functioning of ecosystems, plant-frugivore interactions in fragmented areas have been to date poorly studied. I investigated spatial variation of avian frugivore assemblages and fruit removal by dispersers and predators from Mediterranean myrtle shrubs (Myrtus communis) in relation to the degree of fragmentation and habitat features of nine woodland patches (72 plants). The study was conducted within the chronically fragmented landscape of the Guadalquivir Valley (SW Spain), characterized by 1% of woodland cover. Results showed that the abundance and composition of the disperser guild was not affected by fragmentation, habitat features or geographical location. However, individual species and groups of resident/migrant birds responded differently: whereas resident dispersers were more abundant in large patches, wintering dispersers were more abundant in fruit-rich patches. Predator abundances were similar between patches, although the guild composition shifted with fragmentation. The proportion of myrtle fruits consumed by dispersers and predators varied greatly between patches, but did not depend on bird abundances. The geographical location of patches determined the presence or absence of interactions between myrtles and seed predators (six predated and three non-predated patches), a fact that greatly influenced fruit dispersal success. Moreover, predation rates were lower (and dispersal rates higher) in large patches with fruit-poor heterospecific environments (i.e. dominated by myrtle). Predator satiation and a higher preference for heterospecific fruits by dispersers may explain these patterns. These results show that 1) the frugivore assemblage in warm Mediterranean lowlands is mostly composed of fragmentation-tolerant species that respond differently to landscape changes; and 2) that the feeding behaviour of both dispersers and predators influenced by local fruit availability may be of great importance for interpreting patterns of frugivory throughout the study area.
Keywords: Dispersers; fragmentation; patches (voyant); predators; seed dispersal

Factors affecting bird richness in a fragmented cork oak forest in Morocco - Cherkaoui, Imad; Selmi, Slaheddine; Boukhriss, Jihen; Hamid, Rguibi-Idrissi; Mohammed, Dakki (Acta Oecologica, 2009)
The cork oak forest of Ma’amora in north-western Morocco was the largest cork oak forest in the world until the beginning of the 20th century. Due to growing land use for agriculture and urbanization, however, this forest has become fragmented into relatively small and isolated patches. The effects of this fragmentation on the diversity of wild animal communities have never been investigated despite the importance of such investigations in elaborating longterm conservation plans of the biodiversity of this forest system. In this study of a sample of 44 forest patches we assessed the relationships between species numbers of wintering, breeding and spring migrant birds and patch size, shape, isolation and vegetation structure. We found that species richnesses of the three studied bird assemblages were strongly related to local vegetation structure, namely to the diversity and abundance of trees and bushes. Patches with higher diversity and cover of trees and bushes support higher numbers of bird species. However, patch size, shape and isolation were not signiﬁcant predictors of bird richness. These results suggest that bird communities in the studied forest patches were more likely shaped by local habitat suitability rather than the amount of habitat or patch isolation. The results also demonstrate negative effects of current human pressures, namely logging, grazing and disturbance, on the diversity of bird communities in this forest system. This emphasizes the need for urgent management efforts aiming at reducing the negative impacts of forest use by humans on bird diversity in this forest system
Keywords: birds; Cork Oak Forest; fragmentation; Morocco

Factors affecting bird richness in a fragmented cork oak forest in Morocco - Cherkaoui, Imad; Selmi, Slaheddine; Boukhriss, Jihen; Hamid, Rguibi-Idrissi; Mohammed, Dakki (Acta Oecologica, 2009)
The cork oak forest of Ma’amora in north-western Morocco was the largest cork oak forest in the world until the beginning of the 20th century. Due to growing land use for agriculture and urbanization, however, this forest has become fragmented into relatively small and isolated patches. The effects of this fragmentation on the diversity of wild animal communities have never been investigated despite the importance of such investigations in elaborating longterm conservation plans of the biodiversity of this forest system. In this study of a sample of 44 forest patches we assessed the relationships between species numbers of wintering, breeding and spring migrant birds and patch size, shape, isolation and vegetation structure. We found that species richnesses of the three studied bird assemblages were strongly related to local vegetation structure, namely to the diversity and abundance of trees and bushes. Patches with higher diversity and cover of trees and bushes support higher numbers of bird species. However, patch size, shape and isolation were not signiﬁcant predictors of bird richness. These results suggest that bird communities in the studied forest patches were more likely shaped by local habitat suitability rather than the amount of habitat or patch isolation. The results also demonstrate negative effects of current human pressures, namely logging, grazing and disturbance, on the diversity of bird communities in this forest system. This emphasizes the need for urgent management efforts aiming at reducing the negative impacts of forest use by humans on bird diversity in this forest system
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS
Keywords: birds; Cork Oak Forest; fragmentation; Morocco

Gall wasps and their parasitoids in cork oak fragmented forests - CHUST, GUILLEM; GARBIN, LUCAS; PUJADE-VILLAR, JULI (Ecological Entomology, 2007)
Abstract 1. This paper explores the potential effects of host-plant fragmentation on cork oak gall wasp populations (Cynipidae, Hymenoptera) and on their predators, lethal inquilines, and parasitoids. To address this objective, galls were collected across a gradient of cork oak (Quercus suber) forest fragmentation in the East Pyrenees (Albera, Spain), and they were incubated to obtain the parasitism rates. 2. Two hypotheses were tested: (1) Host-plant fragmentation may induce a decline in gall wasp populations because of area and isolation effects on local extinction and dispersal; as a consequence of that, parasitoids may decline even more strongly in fragmented habitats than their prey. (2) Host-plant fragmentation may cause a decline in gall wasp parasitoid populations that, in turn, can lead to an ecological release in their prey populations. 3. Among the eight cork oak gall wasps sampled in the study area of Albera, the gall abundances of three species (Callirhytis glandium, Callirhytis rufescens, and Andricus hispanicus) were significantly related to forest fragmentation. The overall abundance of gall wasps was affected by a radius of ≈ 890 m surrounding landscape, presenting constant abundances with forest loss until forest cover is reduced at ≈ 40%; below that value the abundance increased rapidly. Three inquilines and 23 parasitoids species were recorded after gall incubation. In 25 cases, species of inquilines and parasitoids were newly recorded for the corresponding host in the Iberian peninsula. 4. Although the overall parasitism rate was high (1.1), it was uncorrelated with fragmentation and with overall cynipid abundance. These results indicate that host-plant fragmentation was correlated with higher abundance of gall wasps, whereas the parasitism rate could not explain this hyper-abundance in small forest fragments.
Keywords: Cork oak; fragmentation; gall wasp; parasitism rate; parasitoid; Pyrenees; Quercus suber

Gall wasps and their parasitoids in cork oak fragmented forests - CHUST, GUILLEM; GARBIN, LUCAS; PUJADE-VILLAR, JULI (Ecological Entomology, 2007)
Abstract 1. This paper explores the potential effects of host-plant fragmentation on cork oak gall wasp populations (Cynipidae, Hymenoptera) and on their predators, lethal inquilines, and parasitoids. To address this objective, galls were collected across a gradient of cork oak (Quercus suber) forest fragmentation in the East Pyrenees (Albera, Spain), and they were incubated to obtain the parasitism rates. 2. Two hypotheses were tested: (1) Host-plant fragmentation may induce a decline in gall wasp populations because of area and isolation effects on local extinction and dispersal; as a consequence of that, parasitoids may decline even more strongly in fragmented habitats than their prey. (2) Host-plant fragmentation may cause a decline in gall wasp parasitoid populations that, in turn, can lead to an ecological release in their prey populations. 3. Among the eight cork oak gall wasps sampled in the study area of Albera, the gall abundances of three species (Callirhytis glandium, Callirhytis rufescens, and Andricus hispanicus) were significantly related to forest fragmentation. The overall abundance of gall wasps was affected by a radius of ≈ 890 m surrounding landscape, presenting constant abundances with forest loss until forest cover is reduced at ≈ 40%; below that value the abundance increased rapidly. Three inquilines and 23 parasitoids species were recorded after gall incubation. In 25 cases, species of inquilines and parasitoids were newly recorded for the corresponding host in the Iberian peninsula. 4. Although the overall parasitism rate was high (1.1), it was uncorrelated with fragmentation and with overall cynipid abundance. These results indicate that host-plant fragmentation was correlated with higher abundance of gall wasps, whereas the parasitism rate could not explain this hyper-abundance in small forest fragments.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cork oak; fragmentation; gall wasp; parasitism rate; parasitoid; Pyrenees; Quercus suber

Factors affecting bird communities in fragments of secondary pine forests in the north-western Mediterranean basin - Brotons, L.; Herrando, S. (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2001)
We assessed the influence of size, extent of isolation and vegetation structure of secondary forest fragments on the richness and species composition of breeding bird communities in a sample of pine forest fragments surrounded by an agricultural matrix in the north-western Mediterranean basin. Fragment size was the main predictor of bird's occurrence, since it accounted for 70 % of the model variation. Isolation was also a valuable predictor of species occurrence, especially for forest specialists. Finally, subarboreal vegetation such as holm oak and a well-developed tree layer of large pines favoured forest species occurrence. Therefore, in spite of the long history of human impact, forest birds in Mediterranean mosaics are sensitive to both habitat loss and isolation of remnant patches in a similar manner to the patterns found in other temperate fragmented landscapes where human impact is more recent. (C) 2001 Editions scientifiques et medicales Elsevier SAS.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75015 PARIS, FRANCE publisher: GAUTHIER-VILLARS/EDITIONS ELSEVIER
Keywords: birds; fragmentation; isolation; Mediterranean mosaics; vegetation structure

Factors affecting bird communities in fragments of secondary pine forests in the north-western Mediterranean basin - Brotons, L; Herrando, S (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2001)
We assessed the influence of size, extent of isolation and vegetation structure of secondary forest fragments on the richness and species composition of breeding bird communities in a sample of pine forest fragments surrounded by an agricultural matrix in the north-western Mediterranean basin. Fragment size was the main predictor of bird's occurrence, since it accounted for 70 % of the model variation. Isolation was also a valuable predictor of species occurrence, especially for forest specialists. Finally, subarboreal vegetation such as holm oak and a well-developed tree layer of large pines favoured forest species occurrence. Therefore, in spite of the long history of human impact, forest birds in Mediterranean mosaics are sensitive to both habitat loss and isolation of remnant patches in a similar manner to the patterns found in other temperate fragmented landscapes where human impact is more recent. (C) 2001 Editions scientifiques et medicales Elsevier SAS.
Keywords: birds; fragmentation; isolation; Mediterranean mosaics; vegetation structure

Functional groups in phytoecology: an application to the study of isolated plant communities in Mediterranean France - Médail, F; Roche, Philip; Tatoni, Thierry (Acta Oecologica, 1998)
e main objective of this study is to compare functional patterns versus plant composition in holm-oak forest isolates from two sites of Provence (Mediterranean France), on siliceous (Maures) or calcareous substrates (Luberon). In order to define plant functional groups, 9 traits out of a total of 71 attributes, were used. Twenty functional groups were defined with predominantly vegetative traits. Within each site, edges and forested core areas refer to different functional groups, in relation to the isolate structure and disturbance effects. In siliceous Provence, a higher structural and functional diversity occurs inside isolates, whereas on calcareous substrate, the diversity of plant functional groups which charac- terizes edges, is as important as in internal parts of isolates. Functional diversity does not necessarily follow the same patterns as the specific diversity, which is always greater in edges. Thus, the use of some sets of attributes, resulting from evolutionary trade-off between plants and their environment, can provide a better understanding of ecological consequences of disturbances. 0
Keywords: biological conservation; disturbances; ecosystems; fragmentation; functional diversity; Functional groups; Mediterranean-type ecosystems; terrestrial islands